2022
DOI: 10.1093/bfgp/elac025
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping and grading of lower-grade gliomas using integrated feature selection and support vector machine

Abstract: Classifying lower-grade gliomas (LGGs) is a crucial step for accurate therapeutic intervention. The histopathological classification of various subtypes of LGG, including astrocytoma, oligodendroglioma and oligoastrocytoma, suffers from intraobserver and interobserver variability leading to inaccurate classification and greater risk to patient health. We designed an efficient machine learning-based classification framework to diagnose LGG subtypes and grades using transcriptome data. First, we developed an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Joshi et al 22 proposed a two-stage ensemble for glioma detection and grading based on clinical and histological data. Munquad et al 23 employed a correlation-based feature selection scheme and an SVM to predict LGG and subtypes, achieving an average accuracy of 91%. Ren et al 24 predicted IDH1 (isocitrate dehydrogenase 1)…”
Section: Introductionmentioning
confidence: 99%
“…Joshi et al 22 proposed a two-stage ensemble for glioma detection and grading based on clinical and histological data. Munquad et al 23 employed a correlation-based feature selection scheme and an SVM to predict LGG and subtypes, achieving an average accuracy of 91%. Ren et al 24 predicted IDH1 (isocitrate dehydrogenase 1)…”
Section: Introductionmentioning
confidence: 99%
“…Each subtype has distinct molecular features, and they can be classified using genomics and epigenomics profiles. Despite the presence of intratumor molecular heterogeneity, recent research has shown that deep learning (DL) and machine learning (ML)-based methods may accurately identify glioma subtypes [ 6 , 7 ]. Due to distinct molecular characteristics, the subtypes of glioma have different clinical outcomes and responses to treatment, highlighting the importance of personalized medicine for brain cancer treatment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, machine learning (ML)-based methods could detect key features from complex datasets and have been popular applications in clinical cancer research in recent years, such as early diagnosis, subtype identification, prognosis prediction, and so on ( 20 ). It has been used to classify various cancer subtypes, for example, breast cancer ( 21 ), adult T-cell leukemia/lymphoma ( 22 ), kidney cancer ( 23 ), and glioma ( 24 ). The application of ML for cancer subtype identification will enable accurate diagnosis and regard to the clinical management of patients.…”
Section: Introductionmentioning
confidence: 99%